Biocide effects of volatile organic compounds produced by potential biocontrol rhizobacteria on Sclerotinia sclerotiorum - Giorgio, Annalisa; De Stradis, Angelo; Lo Cantore, Pietro; Iacobellis, Nicola S. (Frontiers in Microbiology, 2015)
Six rhizobacteria isolated from common bean and able to protect bean plants from the common bacterial blight causal agent, were in vitro evaluated for their potential antifungal effects toward different plant pathogenic fungi, mostly soil-borne. By dual culture assays, the above bacteria resulted producing diffusible and volatile metabolites which inhibited the growth of the majority of the pathogens under study. In particular, the latter substances highly affected the mycelium growth of Sclerotinia sclerotiorum strains, one of which was selected for further studies either on mycelium or sclerotia. Gas chromatographic analysis of the bacterial volatiles led to the identification of an array of volatile organic compounds (VOCs). Time course studies showed the modification of the VOCs profile along a period of 5 days. In order to evaluate the single detected VOC effects on fungal growth, some of the pure compounds were tested on S. sclerotiorum mycelium and their minimal inhibitory quantities were determined. Similarly, the minimal inhibitory quantities on sclerotia germination were also defined. Moreover, observations by light and transmission electron microscopes highlighted hyphae cytoplasm granulation and ultrastructural alterations at cell organelles, mostly membranes, mitochondria and endoplasmic reticulum. The membranes appeared one of the primary targets of bacterial volatiles, as confirmed by haemolytic activity observed for the majority of pure VOCs. However, of interest is the alteration observed on mitochondria as well.